FRI0448 Secukinumab Provides Sustained Improvements in The Signs and Symptoms of Active Psoriatic Arthritis: 2-Year Efficacy and Safety Results from The Phase 3 Randomised, Double-Blind, Placebo-Controlled Trial, Future 1. (15th July 2016) - Kavanaugh, A.; Mease, P.; Reimold, A.; Tahir, H.; Rech, J.; Hall, S.; Geusens, P.; Wang, Z.; Mpofu, S.; ,
Abstract : Background: Secukinumab, an anti–interleukin-17A monoclonal antibody, provided rapid and significant improvements in multiple clinical domains of psoriatic arthritis (PsA) including, signs and symptoms, joint structural damage, physical function, and quality of life, through 52 weeks (wks) in the Phase 3 FUTURE 1 study (NCT01392326 ). 1 Objectives: To assess the long-term efficacy and safety of secukinumab in patients (pts) with PsA treated for up to 104 wks in FUTURE 1. Methods: 606 adults with active PsA were randomised to secukinumab or placebo (PBO). Secukinumab pts received a 10 mg/kg i.v. loading dose at baseline (BL), Wks 2 and 4, followed by 150 mg s.c. (IV→150 mg) or 75 mg s.c. (IV→75 mg) every 4 wks from Wk 8. PBO was given on the same dosing schedule. At Wk 16, PBO-treated pts were re-randomised to receive secukinumab 150 or 75 mg s.c. from either Wk 16 or Wk 24, based on clinical response. Clinical assessments at Wk 104 included: ACR 20/50/70, PASI 75/90, DAS28-CRP, SF-36 PCS, HAQ-DI, mTSS, dactylitis, and enthesitis. Efficacy variables are presented from those pts originally randomised to secukinumab. Multiple imputation (binary variables) and a mixed-effect model repeated measures (continuous variables) were used for analyses at Wk 104. mTSS data are as observed. Results: Overall, 476 pts (78.5%) completed 104 wks of study (167 [82.7%] pts in IV→150 mg group; 155 [76.7%] in IV→75 mg group). At Wk 104, ACR 20/50/70 response rates were 66.8/39.0/22.4% with IV→150 mg and 58.6/29.7/17.6% with IV→75 mg, respectively. Sustained clinical improvements with secukinumab through Wk 104 were observed across other clinically important domains of PsA (Table ). Responses were sustained through Wk 104 in pts naïve to anti-TNF therapy and in those with an inadequate response or intolerance to these agents (anti-TNF-IR). ACR20 response rates at Wk 104 in anti-TNF-naïve pts were 75.2% and 63.7% with IV→150 mg and IV→75 mg, respectively; corresponding rates in anti-TNF-IR pts were 48.0% and 46.9%. No radiographic disease progression (≤0.5 change in mTSS) was observed between BL and Wk 104 in 84.6% of x-ray completers in the IV→150 mg and 83.9% in the IV→75 mg groups. Over the entire study period (mean exposure to secukinumab of 627.1 days) the type, incidence and severity of AEs were consistent with that reported previously. Infections and infestations were the most common AEs observed with secukinumab (67.9 per 100 pt-years). No cases of TB were reported. Malignant/unspecified tumours and major adverse cardiac events occurred at a rate of 0.6 and 0.7 per 100 pt-years, respectively with secukinumab. No suicides were recorded in secukinumab-treated patients. Conclusions: Secukinumab provided sustained improvements in signs and symptoms and multiple clinical domains of active PsA in pts who completed 2 years of therapy. Secukinumab was well tolerated with a safety profile consistent with that previously reported. References: Mease P et al. N Engl J Med 2015; 373:1329–39 Disclosure of Interest: A. Kavanaugh Consultant for: Novartis, P. Mease Grant/research support from: Abbvie, Amgen, BMS, Celgene, Crescendo Bioscience, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, Consultant for: Abbvie, Amgen, BMS, Celgene, Crescendo Bioscience, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, Speakers bureau: Abbvie, Amgen, BMS, Celgene, Crescendo Bioscience, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, A. Reimold Grant/research support from: AbbVie, H. Tahir Speakers bureau: Novartis, Eli Lilly, and Abbvie, J. Rech Speakers bureau: Abbvie, BMS, Celgene, Fresenius, medicap, MSD, Novartis, Pfizer, and Roche, S. Hall: None declared, P. Geusens Grant/research support from: Pfizer, Abbott, Lilly, Amgen, MSD, Will, Bio Minerals and Roche, Speakers bureau: Pfizer, Abbott, Lilly, Amgen, MSD, Will, Bio Minerals and Roche, Z. Wang Employee of: Novartis, S. Mpofu Shareholder of: Novartis, Employee of: Novartis